Pengaruh Pendidikan Kewirausahaan terhadap Perilaku Berwirausaha melalui Minat Berwirausaha Peserta Didik SMKN Manonjaya - Hani Aliya Wardani; Azizah Fauziyah; Nizza Nadya Rachmani (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
The competitive business world demands that young people possess an entrepreneurial spirit, yet student interest in entrepreneurship remains low. This situation highlights the importance of entrepreneurship education in fostering interest and shaping entrepreneurial behavior. This study was conducted to examine the effect of entrepreneurship education on entrepreneurial behavior through entrepreneurial interest. A quantitative method with descriptive and verification approaches was employed. The study involved 84 students from the 2023/2024 class of SMKN Manonjaya. Data were collected using a questionnaire. The results showed that entrepreneurship education influenced entrepreneurial behavior through entrepreneurial interest by 48.1%, while the remaining 51.9% was likely affected by other factors.